Analysis Of Accounting Information Systems For Price Changes At Indomaret In Sungai Selayur Village, Kalidoni Palembang - Alwi Alwi (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
The aims of this research is to find out how to apply accounting information system analysis to price changes in Indomaret, Sungai Selayur Kalidoni Village, Palembang. This is caused by sudden price changes, inappropriate discounts, and differences between the cashier's price and the price tag. By using qualitative methods, namely descriptive analysis which is based on depictions that support the analysis.The results of this research show that price changes using a computer-based accounting information system have run well and smoothly. Price changes are a normal thing that happens in the market and in companies, especially at Indomaret. Because this company itself also adjusts prices on the market. If the market price goes up/down, Indomaret also adjusts the price. The ongoing price change process is also carried out using an online system, all cashier computers are connected to the head office computer and automatically know the transactions that come in every day.